Riscos ocupacionais, danos no material genético e estresse oxidativo frente à exposição aos resíduos de gases anestésicos - Lucio, Lorena M.C. [UNESP]; Braz, Mariana Gobbo [UNESP]; do Nascimento Junior, Paulo [UNESP]; Braz, José Reinaldo C. [UNESP]; Braz, Leandro Gobbo [UNESP] (Elsevier, 2018)
Background and objectives The waste anesthetic gases (WAGs) present in the ambient air of operating rooms (OR), are associated with various occupational hazards. This paper intends to discuss occupational exposure to WAGs and its impact on exposed professionals, with emphasis on genetic damage and oxidative stress. Content Despite the emergence of safer inhaled anesthetics, occupational exposure to WAGs remains a current concern. Factors related to anesthetic techniques and anesthesia workstations, in addition to the absence of a scavenging system in the OR, contribute to anesthetic pollution. In order to minimize the health risks of exposed professionals, several countries have recommended legislation with maximum exposure limits. However, developing countries still require measurement of WAGs and regulation for occupational exposure to WAGs. WAGs are capable of inducing damage to the genetic material, such as DNA damage assessed using the comet assay and increased frequency of micronucleus in professionals with long‐term exposure. Oxidative stress is also associated with WAGs exposure, as it induces lipid peroxidation, oxidative damage in DNA, and impairment of the antioxidant defense system in exposed professionals. Conclusions The occupational hazards related to WAGs including genotoxicity, mutagenicity and oxidative stress, stand as a public health issue and must be acknowledged by exposed personnel and responsible authorities, especially in developing countries. Thus, it is urgent to stablish maximum safe limits of concentration of WAGs in ORs and educational practices and protocols for exposed professionals.
Occupational hazards, DNA damage, and oxidative stress on exposure to waste anesthetic gases
Keywords: Environment pollution; Genomic instability; Genotoxicity testing; Inhaled anesthetics; Occupational exposure; Oxidative stress